Prognostic factors for surgical treatment of prolactin-secreting pituitary adenomas - Voznyak, Oleksandr; Zinkevych, Iaroslav; Lytvynenko, Andrii; Hryniv, Nazarii; Ilyuk, Roman; Kobyliak, Nazarii (Frontiers in Surgery, 2024)
Introduction: Usually, prolactinomas are treated with dopamine agonists (DA). Surgery is considered an option when the patient cannot bear or does not respond positively to DA therapy.Aim: This study aims to determine the early and late outcomes of surgery, with particular emphasis on developing prognostic factors for surgical treatment and analyzing risk factors affecting the recurrence of hyperprolactinemia and prolactinoma.Material and methods: This retrospective study was conducted at the Feofaniya Clinical Hospital of the State Administration of Affairs (Kyiv, Ukraine), evaluating 109 patients' records from 2009 to 2019. The main patients' inclusion criteria were: serum prolactin (PRL) level of more than 100 ng/ml, presence of pituitary adenoma (PA) on MRI, histologically approved PA by microscopy. According to the size of the prolactin-secreting PA (PSPAs) the selected 109 patients were divided into two groups: micro-(≤10 mm, n=75) and macroadenoma group (10-40 mm, n=34).Results: 1 month after the operation, PRL levels decreased by 87% (p<0.001), 12 months -by 93% (p<0.001). After receiving surgery and DA therapy for 12 months 77.1% of patients achieved biochemical remission. Out of the total number of patients observed, 15.6% (n=17) had a Knosp score greater than 3. Additionally, in the macroadenoma group, the percentage of patients with a Knosp score greater than 3 was 41,2 %, which was significantly higher as compared to the microadenoma group (4%, p<0.001). In patients with microadenomas a weak reverse correlation between patients' age (r=-0.258, p<0.026) and positive with tumor size (r=0.251, p<0.030) was revealed. In the macroadenoma group significant association was found only between preoperative serum PRL level and tumor size (r = 0.412, p<0.016). The preoperative PRL can be used as a diagnostic marker for lack of early biochemical remission in patients with PSPAs with diagnostic accuracy 66.9 %.This study found that primary transsphenoidal surgery is an effective treatment in reaching PRL level control in patients with both micro-and macroprolactinomas. The correct and thorough selection of candidates for surgery is crucial to achieve postoperative serum PRL normalization in the vast majority of patients.